2020
DOI: 10.1021/acssuschemeng.0c07086
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid-Mediated Preparation of Noncytotoxic Hemocompatible Stable DNA−ε-Poly-l-lysine Polyplexes: A New Sustainable Approach for the Bulk Production of Potential Nonviral Vectors for Gene Delivery Applications

Abstract: Nonviral vectors are gaining importance as gene delivery systems. However, to meet the large-scale applications, their sustainable production is of utmost importance. Hence, a cost-effective and one-pot strategy for their bulk production is desirable. Herein, a sustainable method for the facile production of nonviral gene vectors, using ε-poly-l-lysine and DNA, having the potential for gene delivery applications was developed using ionic liquids. The hemocompatible nanosized negatively charged polyplexes thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…The zeta potential values were maintained at approximately +5 mV, and the N/P ratio increased to 20. This result is consistent with a previous study in which Bhatt et al reported a charge of +4.47 mV for the ε-PLL aqueous solution [ 44 ].…”
Section: Discussionsupporting
confidence: 94%
“…The zeta potential values were maintained at approximately +5 mV, and the N/P ratio increased to 20. This result is consistent with a previous study in which Bhatt et al reported a charge of +4.47 mV for the ε-PLL aqueous solution [ 44 ].…”
Section: Discussionsupporting
confidence: 94%
“…Syntheses of polymers from the AMDP raw material were investigated. ε-PL, which has primary amino groups, is a polypeptide obtained by microbial fermentation and is biodegradable; it is usually combined with other polymers to form films. Herein, we attempted to prepare ε-PL-based films via condensation reactions with different AMDP ratios (0.2, 2.4, and 7.2 wt % relative to the ε-PL weight) (Figure a). The viscous ε-PL liquid reacted with AMDP in the presence of the condensing agent DMT-MM, and the product was purified by dialysis and lyophilized to produce powdered samples.…”
Section: Resultsmentioning
confidence: 99%
“…ILs have properties such as non-flammability, low vapor pressure, low melting point, excellent thermal and electrochemical stability, high conductivity, high stabilization of specific solutes and the ability to recycle [99]. By using various combinations of cations and anions, ILs have a wide range of applications in the fields of lubricants and additives (lubricants and fuel additive) [100,101], electroelastic material (artificial muscles and robotics) [102], analytics [103][104][105], solvents for processing [106][107][108][109][110][111][112][113][114], liquid crystals (displays) [115,116], heat storage (thermal fluids) [117], electrolytes [118][119][120], and separation (gas separations, extractive distillation, extraction, and membranes) [121][122][123].…”
Section: Ionic Liquids and Deep Eutectic Solventsmentioning
confidence: 99%